Origin of Incremental Step Pulse Programming (ISPP) slope degradation in charge trap nitride based multi-layer 3D NAND flash. (January 2021) - Nam, Kihoon; Park, Chanyang; Yoon, Jun-Sik; Jang, Hyundong; Park, Min Sang; Sim, Jaesung; Baek, Rock-Hyun
Highlights: Origins of ISPP slope degradation from the charge trap nitride in 3D NAND Flash memory were investigated. As electron trap density increases, the ISPP slope is stable but excessive one causes degradation. As electron trap energy level increases, the ISPP slope is improved but erase speed to be concerned. Depositing suitable trap density and energy level in the nitride improves program efficiency. Abstract: We analyzed Incremental Step Pulse Programming (ISPP) slope degradation to improve the program efficiency of 3D NAND Flash memory using both measurement and simulation data. The simulation data are calibrated with the measurement data and they are in good agreement. The ISPP slope indicates program efficiency and its ideal value is 1. In reality, however, ISPP slope degradation (<1) occurs in the charge trap flash (CTF) memory and makes program speed slow. Two parameters affecting the ISPP slope degradation are quantitatively investigated: electron trap density ( NT ) and trap energy level ( ET ) of the charge trap nitride (CTN). There are optimal NT and ET fitted with 3D NAND Flash cell providing better program efficiency with lower retention loss. Detailed reasons are physically explained by observing the electron behaviors in various NT and ET values.